Bloom or not to bloom: Understanding the MiR-156 based regulation of flowering genes in rice (Oryza sativa) - Ahmad , Ayaz; Khan, Haris Ahmed; Nadeem, Mawra; Kazmi, Abeer (Journal of Pure and Applied Agriculture, 2023)
Flowering at the proper time is critical for effective sexual reproduction and the subsequent development of seeds and fruits in plants. This entails synchronising flowering with the right season and the plant's developmental history. The cruciform weed Arabidopsis has shown discrete but connected pathways for sensing the primary seasonal cues of day length and low temperature, as well as other local external and internal signals, using genetic and molecular analyses. A common group of genes integrates the balance of signals from these pathways to decide when blooming commences. Billions of people around the world directly or indirectly depend on rice (Oryza sativa) for their daily nutrition needs. To fulfill the demands of the growing population, scientists are looking for ways to improve the yield by tweaking the flowering genes and controlling the expression of the miR156 gene. The circuitry of the miR156 and its effect on flowering is complex and involves various pathways; some of those pathways are yet to be discovered. The most critical interactions in the SPL-miR156 gene result in the plant's shift from vegetative to reproductive phase. This involves several environmental, morphological, and internal factors coherently effect. Future research will look into the importance of these interactions and more yields will follow by manipulating the genetic interactions. This paper is an attempt to understand the complex nature of the SPL-miR156 gene and how it regulates the flowering process. © 2022 Department of Agricultural Sciences, AIOU